Legal Policy Recommendations for Fostering Green Business Development: A Case Study of Enterprises in Vietnam - Tran Thi Bich Nga (Qubahan Academic Journal)
Green growth is one of the development trends many countries worldwide aim for Vietnam; green growth is also gradually becoming inevitable. However, businesses are among the critical subjects contributing to green growth and are still not interested in this trend. Objective: The article aimed to identify the key factors affecting green business development and proposed legal policy implications for green business development. Methodology: The author applied quality and quantitative methods; based on the study goal, the author surveyed 800 managers of green enterprises in five provinces and three cities in Vietnam and used structural equation modelling based on the quantitative research method. Result: The findings explored five critical factors affecting green business development: (1) financial capacity, (2) corporate culture, (3) leadership and business management capacity, (4) mechanisms and policies of the government and localities, and (5) the interaction of components in the business ecosystem. This comprehensive set of recommendations provides a strategic roadmap for Vietnam to foster green business development through effective legal policies. Conclusion: The article's contributions proposed recommendations to management agencies in developing and implementing mechanisms and policies to support and promote businesses to build in a green direction. Implementing these legal policy recommendations can significantly enhance the development of green enterprises in Vietnam. Unique Contribution: The novelty of this study was to supplement and complete the system of criteria for evaluating green business development, which is also the basis for businesses to recognize the effectiveness of current activities. Key Recommendation: From the above results, the author proposed to establish green financing programs, including low-interest loans, grants, and subsidies for green business initiatives to make improvements in each stage of the production process to increase efficiency while minimizing negative impacts on the environment.